RANCANG BANGUN APLIKASI AMBULANCE ONLINE BERBASIS ANDROID - Ruth Damayanti Patricia Simamora; Made Sudarma Sudarma; I Made Arsa Suyadnya (LPPM STMIK STIKOM Indonesia, 2020)
Ambulance is an emergency transportation used by hospitals, health centers, or related agencies that serves to help people who need medical help. Ambulance is supported with medical devices and medical personnel and is used to carry patients from certain locations to other locations. The majority of Indonesians did not know how to call an ambulance when they were in an emergency situation and needed medical personnel. This ignorance can be fatal and can even cause a person to lose life. Based on these problems, this research creates an Android-based Ambulance Online application that equipped with a Geographic Information Services (GIS) by utilizing the map feature that is integrated with the Google Maps API so that it can provide information of ambulance location, customer location and the route of the road between the two locations. This application is also integrated with the notification feature by utilizing FCM (Firebase Cloud Messaging) so that users can find out information and status order in real time. This Ambulance Online application is expected to result an application that can be used by the society as a customer to order an ambulance quickly and efficiently. This application can provide convenience in emergency response services so that it expected to be able to help people in need